2007
DOI: 10.1098/rspb.2007.1187
|View full text |Cite
|
Sign up to set email alerts
|

Human selection and the relaxation of legume defences against ineffective rhizobia

Abstract: Enforcement mechanisms are thought to be important in maintaining mutualistic cooperation between species. A clear example of an enforcement mechanism is how legumes impose sanctions on rhizobial symbionts that fail to provide sufficient fixed N 2 . However, with domestication and breeding in high-soil-N environments, humans may have altered these natural legume defences and reduced the agricultural benefits of the symbiosis. Using six genotypes of soya beans, representing 60 years of breeding, we show that, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
162
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(175 citation statements)
references
References 60 publications
5
162
1
1
Order By: Relevance
“…Lastly, we predict that host-mediated microbiome engineering will often be more efficient using wild hosts rather than hosts that have experienced domestication, or adaptation to microbially depauperate laboratory environments. This is because genes that enable hosts to control interactions with microbes may have been lost during domestication [31,43]), and agricultural soil microbiomes likely varied greatly between successive plant generations in the absence of host-microbiome co-propagation. In contrast to domesticated plants, however, both honeybees and their vertically-transmitted gut microbes may have been shaped by artificial selection during domestication, and both wild and domesticated honeybees may therefore be suitable models for microbiome engineering.…”
Section: Methods Of Host-mediated Microbiome Engineeringmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, we predict that host-mediated microbiome engineering will often be more efficient using wild hosts rather than hosts that have experienced domestication, or adaptation to microbially depauperate laboratory environments. This is because genes that enable hosts to control interactions with microbes may have been lost during domestication [31,43]), and agricultural soil microbiomes likely varied greatly between successive plant generations in the absence of host-microbiome co-propagation. In contrast to domesticated plants, however, both honeybees and their vertically-transmitted gut microbes may have been shaped by artificial selection during domestication, and both wild and domesticated honeybees may therefore be suitable models for microbiome engineering.…”
Section: Methods Of Host-mediated Microbiome Engineeringmentioning
confidence: 99%
“…Compared to wild ancestors, therefore, domesticated plants may have lost the full capacity for host control and symbiont choice to shape their acquired microbiomes [43]. Consequently, host-mediated engineering of microbiomes may be more successful in undomesticated than in domesticated hosts when selecting on such environmentally acquired microbiomes.…”
Section: Domesticated Versus Wild Hostsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kiers et al (2007) showed that newer cultivars of soybeans did not maintain high yields when inoculated with both a good and a bad rhizobial strain, while older cultivars did, possibly indicating that newer cultivars had lost the capacity to sanction. However, this finding is unlikely to explain natural variation in sanction strength.…”
Section: Differences In Sanction Strength: Examples From Other Types mentioning
confidence: 99%